Avaliação do uso do DCP em areias para controle da capacidade de carga em fundações diretas e controle de compactação de aterros - Benevides, Larissa Dantas (2012)
This work presents results of field and laboratory tests using a Dynamic Cone Penetrometer, DCP. The tests were performed in order to evaluate the use of the equipment in sand for the control of bearing capacity of shallow foundations and fill compaction. For shallow foundations, the laboratory tests were conducted on sand placed in a metallic mould by the method of sand pluviation. Although the results show the inability to reproduce field conditions in the laboratory it was possible to verify the ability of the DCP to identify less resistant soil layers. The DCP tests for the analysis of compaction control were performed in a strong box with inside dimensions of 1,40 m x 1,40 m and 0,70 m in height. The soil layers were compacted with different densities though the use of a vibrating plate in order to obtain correlations between penetration index, DPI, and soil relative density. Other tests were also conducted to assess the influence of soil moisture on tests results. Among other findings, the results showed the great potential for the use of DCP to control the compaction of sand fills